The Contextual Value of Social Capital for Subsistence Entrepreneur Mobility. (September 2015) - Barrios, Andrés; Blocker, Christopher P.
Close-knit relationships are a distinctive facet of subsistence living, in which survival mode entrepreneurship is a way of life. These relationships fuel "bonding social capital" within informal economies as people rely on others to work, consume, and cope with scarce resources. At the same time, policy agendas encourage business growth and social mobility by shifting informal microenterprises into the formal economy. However, success in formalized contexts requires a different form of social capital—that is, "bridging social capital" with people outside one's immediate social network and across institutional structures. Yet policy programs often stop short of addressing how subsistence entrepreneurs manage the inherent tensions across these forms of social capital. As such, this study unpacks the contextual value of social capital using data collected with street vendors in an urban Latin American setting. The analysis identifies four entrepreneurial paths pursued by street vendors and articulates the relative value of bonding and bridging social capital across different economic and social positions. The findings advance insights for a community-centric public policy approach and offer guidance for segmentation and value proposition development within subsistence entrepreneurship programs.